Experiences of bullying behavior among students in the school: A qualitative study - Iyus, Yosep; Ai, Mardhiyah; Suryani, Suryani; Henny Suzana, Mediani; Helmy, Hazmi (Asia Pacific Academy of Science Pte. Ltd., 2024)
The phenomenon of bullying among students in schools has increased rapidly. Cases of bullying among students cause various problems such as stress, depression, anxiety, and even problems with academic abilities. Exploring the experiences of bullying among students is necessary to determine the incidents of bullying experienced by students. The aim of this research is to explore the experiences of bullying experienced by students at school. The method used was qualitative study with semi-structured interviews regarding experiences of bullying among students. The sample used in this research was 10 students aged 15-18 at school in Bandung Barat, West Java, Indonesia who had experienced bullying. The results showed that the experience of bullying in students has three themes, namely verbal bullying, physical bullying, and cyberbullying. Various experiences of bullying in students cause psychological problems. Students become insecure at school because of bullying they have experienced. Bullying can be in the form of harassment, physical humiliation, insults with low grades, and sudden beatings. Bullying victims said that the perpetrators of bullying were mostly upperclassmen to their younger classmates, so bullying was also caused by the power relationship between the perpetrator and the victim. Bullying behavior in schools requires special handling by schools to make policies to prevent bullying. So that further research is needed on the factors that cause bullying in adolescents at school.